Dr. Mateusz Zachara — Deep Plane Facelift — Polanica-Zdrój - Zachara, Mateusz (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Mateusz Zachara, practicing in Polanica-Zdrój, Poland. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003254; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; poland; polanica-zdrój